(untitled) (Journal of Economic Research & Business Administration, 2016)
In a market economy, taxes are main source of funding for the state. The funds give the State an opportunity to carry out social policies, in cluding providing material assistance to those sectors and groups of the population who are unable to secure their existence at a minimum. One of the most common types of taxes of any state is the corporate income tax. In this regard, the present article describes the issues that arise in real business transactions, taking into account corporate income tax, their cal culus. And also because of the imperfection of the methodological basis of taxation, with the tax and accounting laws often do not coincide, and the changes in taxation affect virtually procedure of recording of tax payments.